The Relationship Between Plato’s Letters and His Understanding of Philosophia - Baran Bingöl (Felsefe Arkivi)
This paper aims to reveal the relationship between the 2nd, 7th, and 10th Letters, encompassing “philosophical” content among Plato’s letters, and the dialogues. There is a crucial research gap regarding coherence or incoherence between the letters and the dialogues. Therefore, at least the parts of these letters considered “philosophical” should be translated into Turkish and their consistency with the dialogues clarified. In this paper, I advocate a significant consistency between the dialogues and the letters that must be explored in-depth. The first part of the paper consists of translating the 2nd, 7th, and 10th Letters from Ancient Greek into Turkish and analyzing the relationship between these letters and the dialogues. Especially when the 2nd, 7th, and 10th Letters and dialogues are examined as a whole, it is clear that Plato tries to explain that which is truth-that which is pseudo distinction consistently. This is essential for his system, and on the basis of this distinction, he distinguishes what he means and does not mean by “philosophia” through his relationship with Dionûsios, the king of Surakousa of the period. Burnyeat ironically declares the 7th Letter “pseudo” by claiming that there is no coherence between it and the dialogues and that they even contradict each other, without considering this fundamental distinction between that which is truth-that which is pseudo. The second part of the article is a critique of Myles Burnyeat’s article “The pseudophilosophical digression in Epistle VII,” which posits that the 7th Letter is pseudo.